The complexity of mudstone diagenesis – some insight from the Tøyen Shale, Lower to Middle Ordovician, southern Sweden. (2nd January 2019) - Egenhoff, Sven O.; Fishman, Neil S.; Lowers, Heather A.; Ahlberg, Per
ABSTRACT: The Lower to Middle Ordovician Tøyen Shale in southern Sweden, a biostratigraphically well-dated siliciclastic mudstone unit, shows 18 distinct authigenic cements that include sulfides, carbonates, silicates, clays, and phosphates. Marcasite, sphalerite, galena, and six texturally distinct types of pyrite characterize the sulfides whereas only one type of dolomite and three different generations of calcite are observed in this unit. Quartz, phosphate, and organic matter occur as only one generation each. Authigenic clay minerals are represented by chlorite and kaolinite. The paragenetic sequence of cements is subdivided into the two pre-burial carbonates, succeeded by ten relatively early burial cements, and six late burial cements, the kaolinite being the latest of them all and potentially being of Cretaceous age. Based on textural relationships, the paragenetic sequence of alterations started with dolomite precipitation followed by calcite, and then five different generations of pyrite. All eleven other phases post-date these initial seven cements in the Tøyen Shale.